SUICIDE RISK AMONG NURSING STUDENTS ATTENDING A PUBLIC UNIVERSITY - Diego da Silva Ferreira; Vladson Gouveia Ferreira; Nathanael de Souza Maciel; Francisco Mardones dos Santos Bernardo; Monaliza Ribeiro Mariano Grimaldi; Carolina Maria de Lima Carvalho (Universidade Federal do Paraná, 2023)
Objective: to describe the suicide risk rates in Nursing students from different nationalities in a public university. Method: a cross-sectional study conducted between August and November 2019 in Ceará, Brazil. The students included were those aged at least 18 years old and duly enrolled; the exclusion criteria were as follows: inactive link due to medical leave or course cancellation. The Suicide Risk Index was used for data collection. The following tests were performed: Chi-square; Fisher's Exact and Mann-Whitney. Results: of the 192 participants, 28.6% did not have religious/spiritual factors susceptible of stopping the suicidal act, 12.5% had a family history of suicide, and 2.6% had suicide plans. An association was detected between gender and suicidal potential risk (p>0.000). There was a difference in the suicidal potential risk in relation to gender (p>0.000), nationality (p>0.000) and marital status (p=0.043). Conclusion: the study contributes to a reflection on suicide, to early detection and to understanding the impacts in the university.